GOODWILL OF LIBRARY USERS AND ITS IMPACT ON SERVICES: A STUDY - Rokade, S.M. (International Journal of Research -GRANTHAALAYAH, 2016)
The paper succinctly describes the concept of goodwill, nature and value, intellectual capital resources, viewpoints of library goodwill, perspectives and User’s goodwill and its impacts on functioning of library, services and working staff. It reveals that 64.70 % goodwill generates among the users through maintaining good relations by the library staff, 64% rendering quality services, 92% leadership, promptness, and skillful policy, 84.70 by creating well behaviour with various types of readers, 47.05 % library staff should be punctual in timing with attachment and affinity in public library readers as they comes under the umbrella of grass root users. The goodwill generates 80.83 % intangible asset which invisible and 92.50 % develop publicity of library automatically. It was concluded that goodwill totally depends on the behaviour and prompt services to the users to save their times.